LGBTQ+ Youths' Community Engagement and Resource Seeking Online versus Offline. Issue 4 (2nd October 2019) - McInroy, Lauren B.; McCloskey, Rebecca J.; Craig, Shelley L.; Eaton, Andrew D.
Abstract: LGBTQ+ (lesbian, gay, bisexual, transgender, queer, etc.) youth are at increased risk for negative outcomes. Yet little is known about their engagement with communities and resources that may ameliorate risk, particularly online. Oriented by a uses and gratifications approach, this secondary analysis ( n  = 4, 009) of LGBTQ+ youth (aged 14–29) compares online versus offline experiences. Respondents were significantly more likely to participate in LGBTQ+ communities online. Youth were also more active, and felt safer and more supported, when participating in online LGBTQ + communities. Additionally, respondents sought online information, support, and resources at higher rates than offline. Increased attention toward online programming and resource development is warranted.